2018
DOI: 10.1002/pts.2373
|View full text |Cite
|
Sign up to set email alerts
|

Light barrier properties of extra virgin olive oil (EVOO) glass bottles—Effect of glass colour and decoration

Abstract: The aim of this study was to evaluate the quality of some glass bottles used for extra virgin olive oil (EVOO) related to light barrier properties, including clear and coloured glass in different colour intensities, glass with shrink labels, and external ceramic decoration. Some of these glass bottles available on the Brazilian market were also evaluated for closure integrity and barrier to oxygen, headspace gas atmosphere, and the quality of the product according to legislation. An increase in light barrier p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The similar VOC pattern for HDPE and AT may be linked to the permeability of the HDPE container. It has been demonstrated that plastic materials, conversely to glass, allow for water and oxygen permeability [ 67 ] from the external environment through the packaging and vice versa, thus leading to a similar environment between HDPE and AT storage conditions with an exchange of heat, moisture, and oxygen which in turn leads to oxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The similar VOC pattern for HDPE and AT may be linked to the permeability of the HDPE container. It has been demonstrated that plastic materials, conversely to glass, allow for water and oxygen permeability [ 67 ] from the external environment through the packaging and vice versa, thus leading to a similar environment between HDPE and AT storage conditions with an exchange of heat, moisture, and oxygen which in turn leads to oxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the transparent materials LDPE/EVOH/LDPE and LDPE/PA/LDPE (control), it is observed that from the wavelength from 250 to 800 nm (which includes ultraviolet (<400 nm) and visible light (400–700 nm) (Jaime, Bócoli, Miguel, Ferreira, & Alves, 2018)), high light transmission occurs (90%). In the material PET/LDPE/PA/EVOH/PA/LDPE (control), up to a wavelength of 300 nm, this material had a high light barrier and from 300 to 800 nm, with 90% transmittance.…”
Section: Resultsmentioning
confidence: 99%